Numerical modeling for efficiency and endurance assessment of an indirect mitral annuloplasty device. (December 2022) - Galili, Lee; Weissmann, Jonathan; White Zeira, Adi; Marom, Gil
Abstract: In recent years, several transcatheter systems have been introduced for treatment of common mitral regurgitation (MR). Such a system that is based on indirect mitral annuloplasty (IMA) is currently indicated for functional MR. Very few clinical studies have been performed to assess the efficiency and durability of such devices, despite their high risk of fracture resulting from ongoing exposure to large cyclic deformations. In this study, numerical models of moderate primary MR were created to test the implantation procedure of a customized IMA device and its sealing efficiency. The ability of the implanted device to reduce systolic leakage was evaluated and affirmed with a model of a more generic device. The long-term durability of the device was tested using a range of Nickel Titanium material properties. Our results demonstrated a considerable reduction in leakage for both the simplified generic device and the more detailed customized device models. The device met different fatigue criteria, confirming its resiliency and safety even after 10 years, even under the harsher conditions of primary MR. This is the first study to assess the performance and fatigue risk of IMA devices for the treatment of more complicated MR conditions. These findings may pave the way for further research to ultimately consider the device in selective cases of PMR. Graphical abstract: Image 1